Growth chemistry and electrical performance of ultrathin alumina formed by area selective vapor phase infiltration - Snelgrove, Matthew; Mani Gonzalez, Pierre Giovanni; McFeely, Caitlin; Hughes, Gregory; Weiland, C; Woicik, Joshep; Shiel, Kyle; Ornelas, Carlos; Solis-Canto, Óscar; Cherkaoui, K; Hurley, P; Yadav, Pravind; et al. (2022)
The growth chemistry and electrical performance of 5 nm alumina films, fabricated via the area-selective vapor phase infiltration (VPI) of trimethylaluminum into poly(2-vinylpyridine), are compared to a conventional plasma enhanced atomic layer deposition (PEALD) process. The chemical properties are assessed via energy dispersive X-ray spectroscopy and hard X-ray photoelectron spectroscopy measurements, while current – voltage dielectric breakdown and capacitance – voltage analysis is undertaken to provide electrical information of these films for the first time. The success and challenges in dielectric formation via polymer VPI, the compatibility of pyridine in such a role, and the ability of the unique and rapid grafting-to polymer brush method in forming coherent metal oxides is evaluated. It was found that VPI made alumina fabricated at temperatures between 200 and 250 °C had a consistent breakdown electrical field, with the best performing devices possessing a к value of 5.9. The results indicate that the VPI approach allows for the creation of alumina films that display dielectric properties of a comparable quality to conventional PEALD grown films.